Development and validation of HPLC and UV spectrophotometric methods for the determination of lumiracoxib in tablets - T.S. Moreira; M.B.R. Pierre; C.A.M. Fraga; V.P. Sousa (São Paulo State University (UNESP), 2008)
In this study, two methods, based on highperformance liquid chromatography (HPLC) and UV spectrophotometry, were developed and validated for the quantitative determination of lumiracoxib in tablets. The HPLC was carried out on a column of propylsulfonic acid bonded to silica gel (250 x 4.6 mm; 5 μm), with a mobile phase of phosphate buffer (pH 7.4; 10 mM)-water-acetonitrile (10:40:50, v/v/v) flowing at 1.0 mL/min and detection of the drug at 278 nm. The UV method was based on absorbance at 275 nm, with ethanol as solvent. Both assays were linear over the concentration range of 2-30 μg/mL (R≈0.999), as well as accurate and precise, with recoveries between 98 and 100% and relative standard deviation (%RSD) < 2.0%. The proposed methods are highly sensitive, precise and accurate and were successfully applied to the quantitation of lumiracoxib in the commercial formulation. The spectrophotometric method is a simple, cheap and less time-consuming method. However, the chromatographic method is selective for the determination of the degradation products of lumiracoxib.